Associations of the Oxford Knee Score and knee arthroplasty revision at long‐term follow‐up. Issue 1 (19th January 2023) - Tay, Mei Lin; Monk, A. Paul; Frampton, Chris M.; Hooper, Gary J.; Young, Simon W.
Abstract: Background: Self‐reported outcome measures are increasingly being collected for healthcare evaluation therefore it is prudent to understand their associations with patient outcomes. Our aims were to investigate: (1) if Oxford Knee Score (OKS) is associated with impending revision at long‐term (5 and 10 years) follow‐up, and (2) if decreased OKS at subsequent follow‐ups is associated with higher risk of revision. Patients and Methods: All total knee (TKAs) and unicompartmental knee arthroplasties (UKAs) between 1999 and 2019 in the New Zealand Joint Registry with an OKS at 6 months (TKA n = 27 708, UKA n = 8415), 5 years (TKA n = 11 519, UKA n = 3365) or 10 years (TKA n = 6311, UKA n = 1744) were included. Logistic regression determined associations of the OKS with revision within 2 years of each score. Change in OKS between timepoints were compared with revision risk. Results: For every one‐unit increase in OKS, the odds of TKA and UKA revision decreased by 10% and 11% at 6 months, 10% and 12% at 5 years and 9% and 5% at 10 years. For both procedures a decrease of seven or more OKS points from previous follow‐up was associated with higher risk of revision (5 years: TKA 4.7% versus 0.5%, UKA 8.7% versus 0.9%; 10 years: TKA 4.4% versus 0.7%, UKA 11.3% versus 1.5%; all P < 0.01). Conclusion: The OKS had a strong negative association with risk of impending TKA and UKA revision from early to long‐term (10+ years) follow‐up. A decrease of seven or more points when compared with the previous follow‐up was also associated with higher revision risk. Abstract : The OKS had a strong negative association with risk of impending TKA and UKA revision from early to long‐term (10+ years) follow‐up. A decrease of seven or more points when compared with the previous follow‐up was also associated with higher revision risk. The associations of the score with revision suggest that the OKS has some utility as a screening tool for patient surveillance, and the OKS thresholds with varying sensitivity and specificity presented here provide some useful estimates that can help inform clinical practice.